Early interferon-lambda production by human nasal epithelial cells - Korovanenko, Valeriia (Trinity College Dublin. School of Medicine. Discipline of Immunology, 2025)
Nasal epithelial cells serve as a first line of defence against respiratory pathogens, playing a particularly crucial role in the detection and response to viruses that enter the body via the nose. Despite their importance, current research largely overlooks early antiviral responses, particularly within the first hours post-infection. This study aims to address this gap by optimising extraction methods, cell preparation and characterisation of the early immune response in nasal epithelial cells. To achieve this, various techniques for cell isolation, including mechanical dissociation and the use of animal component-free kit, were evaluated for their efficiency and effectiveness. We measured cell yield, viability, and RNA quality across different extraction methods. Our results indicated that while both methods yielded comparable cell counts, the mechanical dissociation was more efficient, cells had less debris and when cultured grew better. They also provided higher RNA concentrations and purity, highlighting its suitability for downstream applications such as gene expression analysis. This study also explores the natural antiviral immune response in nasal epithelial cells by examining differences in immune cell composition and interferon expression in healthy individuals. Participants were recruited through an institutional campaign and ethical approval for the study was obtained from the TCD Research Ethics Committee. Nasal swabs were collected to measure baseline levels of type I and III interferons (IFNs) as well as interferon-stimulated genes (ISGs), followed by stimulation with Poly IC. A novel approach was used in which nasal swab samples were directly stimulated, preserving the cells physiological state. Our findings reveal significant variability in interferon baseline expression and responses across individuals. Type III IFNs responses were detected as early as 4 hours post-stimulation, with correlations observed between the epithelial cell marker EpCAM and IFNL1 expression upon stimulation. Additionally, a negative correlation was found between IFN- (IFNE) and IFN- (IFNL2/3), suggesting a potential regulatory mechanism or competition between these interferons in controlling inflammation and antiviral responses in mucosal tissues. The direct swab stimulation method proved to be an efficient and non- invasive technique for quickly assessing immune responses in vivo, offering a practical alternative to time-consuming culture-based methods.
APPROVED
Keywords: Interferon-lambda; Human nasal epithelial cells; Interferons